The New New Poor Law: A Chapter in the Current Class War Waged from Above - Palmer, Bryan D. (Labour / Le Travail, 2019)
This essay is an attempt to outline recent trends in the criminalization of working-class lives. It casts the net broadly, both historically and geographically, situating capitalist austerity’s recent turn to mass incarceration in the United States and Canada in early 19th-century poor law sensibilities. What is happening now differs from the workhouse regime of industrial capitalism’s new poor law, of course, but it has undoubted connections to this older regime of regulation. The new new poor law of our times is part of a long history of how dispossession has been pivotal to capitalism’s project of uninhibited accumulation and suppression of those driven to defiance and dissent. It reveals how, as profit declines in the productive sphere, incarceration itself can be made to pay. The new new poor law is fundamental to contemporary capitalist political economy as the politics of austerity, the dismantling of the welfare state, and an assault on working-class entitlements and trade unionism are complemented by the rise of a prison-industrial complex. Driven by class antagonisms and racialized scapegoating, the new new poor law inevitably draws into its sphere of influence public-sector workers employed in the criminal justice system. It also unleashes intensified grievances of the incarcerated, stimulating the birth of movements of protest in which prisoners and proletarians search out ways of making common cause.